Złożone nazwy środków czynności we współczesnym języku rosyjskim i ich polskie ekwiwalenty - Kuligowska, Katarzyna (Acta Polono-Ruthenica, 2011)
The author of the article present the ways of profiling of reality by Russian compund names of instruments in comparison to their Polish equivalents. The analysis of the lexical material shows that the majority of Russian nomina instrumenti and their Polish counterparts expose the same or very similar semantic aspects. The differences in the ways of presenting of cognitive content can be observed only in the group of these Russian compound nouns which Polish equivalents belong to the suffixal derivatives.